Training load determining the sport perfomance of the woman race walker to 50 km - Jaroslav Broďáni; Mária Katerinka Czaková (Matej Bel University, 2023)
In the article, we point out the volume training indicators that determined the sports performance of the race walker at 20 and 50 km. The basis of the analysis were the training volume indicators and the annual sport performance. Nonparametric procedures were chosen according to the assessment of the normality of file layout. Differences between the completed volume were evaluated statistically (Z) and substantively ("r"). The nonparametric algorithm CHAID was used for the construction of the regression trees. By the trees method were selected training indicators which showed in the individual training cycles high tightness with race walking performance. The regression model in training cycles YTC 2017/2018 introduced the indicator of intense tempo endurance (walking 4:41-5:00 min.km-1), extensive aerobic endurance (walking 6:00 and more min.km-1) and the running volume indicator. Extended aerobic endurance (walking 5:41-6:00 min.km-1), extensive tempo endurance (walking 5:01-5:20 min.km-1), intense special endurance (walking 4:06-4:20 min.km-1), number of starts and regeneration have been enforced between the predictors of the walking performance in training cycles YTC 2018/2019. The analysis points to the training resources which were most involved in the improvement of the sport performance. Their exact identification will allow the rationalization of the training process in the future, coordinate the conceptual bases of sport preparation and to improve the system of shaping the top condition towards the 2021 Olympics in Tokyo. DOI: https://doi.org/10.24040/sjss.2022.8.2.50-64